2022
DOI: 10.47691/joi.v3.7916
|View full text |Cite
|
Sign up to set email alerts
|

The reverse motion illusion in random dot motion displays and implications for understanding development

Abstract: Across two independent developmental labs, we have been puzzled by the observation that a small proportion of our child and adult participants consistently report perceiving motion in the direction opposite to that presented in random dot motion displays, sometimes even when the motion is at 100% coherence. In this review, we first draw together existing reports of misperceptions of motion direction in random dot displays across observers in a small percentage of trials, before reporting evidence of consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Reverse motion perception has been observed widely with RDK stimuli, and occasionally with sinusoidal gratings. A small number of observers (usually less than 15%) may consistently perceive motion in the opposite direction to the actual dot motion [ 51 ]. Even with RDKs of 100% coherence, similar to the stimuli used in the current study, observers can still show reverse motion perception [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse motion perception has been observed widely with RDK stimuli, and occasionally with sinusoidal gratings. A small number of observers (usually less than 15%) may consistently perceive motion in the opposite direction to the actual dot motion [ 51 ]. Even with RDKs of 100% coherence, similar to the stimuli used in the current study, observers can still show reverse motion perception [ 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The probability of perceiving the actual motion direction presented in an RDK, or the opposite or orthogonal direction, corresponds to the relative strength of motion energy in all perceived directions [ 55 ]. Even RDKs of 100% coherence could contain motion energy in the opposite direction, which might contribute to the reverse motion perception [ 51 ]. The motion energy analysis for our stimuli shows that the net motion energy of retinal images along the vertical dimension was in the opposite direction to internal motion ( S2 Fig ), which could be a source of ambiguity in the direction signal.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that confidence was higher for responses in the antipodal (±π) direction than in orthogonal (±π/2) directions. Manning et al (2022) reviewed a collection of studies, including conference presentations and informal reports of experiments carried out with both adult participants and children, which found that participants in the RDM task sometimes report seeing antipodal motion even when the motion is 100% coherent. They remarked that the phenomenon seems to have been observed much more widely than has been reported in the literature.…”
mentioning
confidence: 99%
“…Despite the clear evidence for ROOD responses both from the data ( Figures 3 , 4 , 6 , and 7 ) and subjective reports, there were not sufficient trials to assess additional properties of these responses, especially whether they vary with direction. Further research would be needed to shine light on the nature of this phenomenon ( Manning, Meier, & Giaschi, 2022 ), for example, by maximizing the number of ROOD by focusing on fewer conditions ( Bae & Luck, 2022 ).…”
Section: Discussionmentioning
confidence: 99%